2005
DOI: 10.2113/176.6.487
|View full text |Cite
|
Sign up to set email alerts
|

Superposition of tectono-thermal episodes in the southern Cantabrian Zone (foreland thrust and fold belt of the Iberian Variscides, NW Spain)

Abstract: The combined use of the illite “crystallinity” Kübler index (KI) and the conodont colour alteration index (CAI) has revealed the existence of three thermal episodes in an area affected by thin-skin tectonics, close to the internal zones of the Variscan orogen in NW Spain. In the southernmost part of the study area, the first episode gave rise to a regional syntectonic Variscan metamorphism. The associated deformation involves the development of a slaty cleavage, which is mainly recognized in Precambrian rocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…Estimated geothermal gradients of 52 °C/km (Botor 2012) are lower than those at other Stephanian basins (Mendez 1985;Frings et al 2004;Ayllon et al 2003) and in the Palaeozoic basement (c. 35 °C/km; Brime et al 2001). Aller et al (2005) argued that increased heat flow due to hydrothermal-fluid circulation was the last important thermal episode in the SCZ, facilitated by pathways along faults. As a consequence, the effects of this episode are irregularly distributed within the basins (Brime et al 2001;Aller et al 2005).…”
Section: Geological Settingmentioning
confidence: 82%
See 4 more Smart Citations
“…Estimated geothermal gradients of 52 °C/km (Botor 2012) are lower than those at other Stephanian basins (Mendez 1985;Frings et al 2004;Ayllon et al 2003) and in the Palaeozoic basement (c. 35 °C/km; Brime et al 2001). Aller et al (2005) argued that increased heat flow due to hydrothermal-fluid circulation was the last important thermal episode in the SCZ, facilitated by pathways along faults. As a consequence, the effects of this episode are irregularly distributed within the basins (Brime et al 2001;Aller et al 2005).…”
Section: Geological Settingmentioning
confidence: 82%
“…In the SCZ, the Stephanian coal-bearing basins are distributed along deep-reaching strike-slip faults formed as a consequence of transtensional movements that migrated westward with time during the late stages of the Variscan orogeny (Aller et al 2005;Colmenero et al 2008). As the Stephanian sedimentary rocks in the basins generally have a higher coal rank than older Palaeozoic sediments in the same region, it has been suggested that the local magmatism (sills and dykes, volcanism) increased thermal maturation (Aller et al 2005;Colmenero et al 2008), producing a coal rank of up to anthracite level (above 2.0 % R r ).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations